Dinamika Pasien dengan Gangguan Skizofrenia - Triandini Paramita; Setyani Alfinuha (LPPM Universitas Proklamasi 45, 2021)
Schizophrenia is a brain disorder that has problems with social functioning, self-care, and difficulty to distinguishing the real world and the imaginary one. This study aims to specify the personality dynamics of people with schizophrenia. In addition, researchers also identified the factors that affect schizophrenia. This research uses case study and qualitative methods with one participant. The participant is a patient diagnosed with schizophrenia at Mental Hospital X. This research is equipped with data from interviews, observations, and several psychological test tools to enrich the research results. The results showed that the conditions and experiences that the participant went through from childhood to adulthood influenced the formation of schizophrenia. Furthermore, there are external factors and internal factors that affect the formation of schizophrenia in the study participants.